Comparative advantage for research and development across industries in OECD countries - Michael Stolpe (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
This paper explores the empirical relevance of the concept of comparative advantage and of the factor proportions theory of international trade and specialisation for the distribution of research and development (R&D) activities across seventeen industries in fourteen OECD member countries over the period from 1970 to 1989. The paper first discusses bivariate correlations between countries' R&D intensities across industries and industries' R&D intensities across countries which confirm that the average R&D intensity is a characteristic feature of individual industries as well as of individual countries. Using the analysis of variance technique, the paper then shows that the type of industry and the country of its location are determinants of the observed human capital intensity in R&D, measured here either by the ratio of university graduates in R&D to other R&D personnel or by the ratio of R&D scientists and engineers to other R&D personnel. Finally, the paper uses multiple regression analysis to examine — separately for each industry in the sample —the impact of a country's human capital endowment, production specialisation, size and of time on the degree to which the country specialises in a particular industry's R&D activities. While the results of these regressions are generally not inconsistent with the factor proportions theory, they do reveal strikingly distinct patterns of R&D specialisation for computers, electrical machinery and radio, television and communication equipment, the industries most closely connected to the fast changing microelectronic technologies.
Keywords: 330; Industrielle Forschung; Humankapital; Internationaler Wettbewerb; Internationale Arbeitsteilung; Außenwirtschaftstheorie; OECD-Staaten